Sudha Murty’s Fictional World and Its Moral Vibes: Exploring Sudha Murty's Moral Blend in Fiction (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Instruction and pleasure have famously been termed, and recognized, as the purposes of literature. All great literature serves these two purposes. Stories and novels written by the well-known Indian writer Sudha Murty are no exception. Sudha Murty is a well-known entrepreneur, social worker and author. In 2006, the government of India honoured her with Padam Shri for her philanthropic work. Among other things, she is known for her campaign to provide all government schools in Karnatka with computer and library facility. She is a prolific writer of fiction both in Cannada and English. On the basis of her wide readership and literary acclaim, she has joined the rank of the writers like Ruskin Bond, R.K. Narayan and Devdutt Pattanaik. She is a household name in India so far as the children’s literature is concerned. She has deservedly received the R.K. Narayan Award for Literature along with many other prestigious awards. She has a way with words and writes in such a smooth and captivating style that not only the children but grown-up people also enjoy reading her stories. This paper is an attempt to show how she uses her simple and unique style to blend morality with fun in such a way as the readers get the message along with enjoyment without being conscious of it.